Tensile testing of sheet metals at elevated temperatures with optical strain rate control - Naumann, David; Merklein, Marion (44th Conference of the International Deep Drawing Research Group (IDDRG 2025), 2025)
The manufacturing of sheet metal parts from lightweight alloys is often restricted due to limited formability of the applied materials at room temperature. To overcome this issue, thermally supported forming processes like hot forming are used. To map and predict the material behaviour in simulations, the materials have to be characterised at elevated temperatures. For the elasto-plastic behaviour, this typically is done by tensile tests. Thereby, dependent of the testing system, inhomogeneous temperature distributions are introduced to the sample unintentionally. This commonly known issue leads to an unintended increase of the strain rate during testing. Optical strain rate controlling (OSRC) is a new approach that enables the determination of the strain hardening behaviour of sheet materials at a constant true strain rate. Hence, in the scope of this contribution, the titanium alloy Ti-6Al-4V, is investigated at temperatures between 600 °C and 900 °C, at strain rates of up to 0.1 s-1. The tensile tests were carried out on a Gleeble 3500 GTC simulator together with an ARAMIS 3D DIC system for the in-situ strain measurement. The deviation of the strain rate evolution was improved up to fourfold by using the OSRC method in comparison to the conventional testing procedur
Keywords: tensile test Gleeble / DIC / strain rate